2014
DOI: 10.1016/j.specom.2013.06.007
|View full text |Cite
|
Sign up to set email alerts
|

Does our speech change when we cannot gesture?

Abstract: Do people speak differently when they cannot use their hands? Previous studies have suggested that speech becomes less fluent and more monotonous when speakers cannot gesture, but the evidence for this claim remains inconclusive. The present study attempts to find support for this claim in a production experiment in which speakers had to give addressees instructions on how to tie a tie; half of the participants had to perform this task while sitting on their hands. Other factors that influence the ease of comm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(41 citation statements)
references
References 32 publications
1
38
2
Order By: Relevance
“…We add this condition as it has been shown that anticipatory postural adjustments (APA's) that arise when moving the upper limbs while standing are dramatically diminished when the body is in a more stable sitting position (Cordo & Nasher, 1982). This could also explain that Krahmer & Swerts (2006) did not find effects of body movements on F0 and intensity measures as their participants were sitting throughout the experiments (also see Hoetjes, Krahmer, & Swerts, 2013). Thus if APA's are driving the current effects on phonation then we would find that the effects of upper limb movements on phonation are absent or diminished in the sitting condition relative to upper limb movement effects on phonation in the standing condition.…”
Section: Pre-registration Confirmatory Studymentioning
confidence: 73%
“…We add this condition as it has been shown that anticipatory postural adjustments (APA's) that arise when moving the upper limbs while standing are dramatically diminished when the body is in a more stable sitting position (Cordo & Nasher, 1982). This could also explain that Krahmer & Swerts (2006) did not find effects of body movements on F0 and intensity measures as their participants were sitting throughout the experiments (also see Hoetjes, Krahmer, & Swerts, 2013). Thus if APA's are driving the current effects on phonation then we would find that the effects of upper limb movements on phonation are absent or diminished in the sitting condition relative to upper limb movement effects on phonation in the standing condition.…”
Section: Pre-registration Confirmatory Studymentioning
confidence: 73%
“…In line with our previous study on repeated references (Hoetjes et al, 2015), and following many other studies (e.g., Alibali et al, 2001;Bard et al, 2000;Bavelas et al, 2008;de Ruiter et al, 2012;Hoetjes et al, 2014;Mol et al, 2009), we include visibility as an additional variable in the design of our production experiment (experiment I). We do this in such a way that one group of participants will be able to see each other (mutual visibility), while the other group are prevented to do so using a screen (no visibility).…”
Section: On the Role Of Visibilitymentioning
confidence: 99%
“…As mentioned above, following Hoetjes et al (2015), and many other related studies (e.g., Alibali et al, 2001;Bavelas et al, 2008;de Ruiter et al, 2012;Hoetjes et al, 2014;Mol et al, 2009), we added visibility as an additional variable to the design, in such a way that one group of participants could see each other during the experiment, while the other group was prevented from doing so by an opaque screen which was placed in between them.…”
Section: The Present Studymentioning
confidence: 99%
“…Thus evidence is still lacking for theories that propose a pivotal role for gesture in speech-production processes (e.g., Krauss, 1998;McNeill, 1992McNeill, , 2005. Indeed, Hoetjes, Krahmer, & Swerts (2014) conclude that there is little convincing evidence for direct (beneficial) effects of gesture on speech properties (e.g., fluency, acoustic parameters), especially in the case of spontaneous gestures in natural contexts.…”
Section: Introductionmentioning
confidence: 96%
“…Pouw, van Gog, Zwaan, Paas, 2017), so as to successfully summon concepts that the speech production system fails to achieve unimodally (i.e., semantic fluency). As such, it has been theorized that primarily semantics are in gesture's functional domain (e.g., Hoetjes et al, 2014;Hosetter & Alibali, 2008). Of course, there has been research on non-semantic aspects of the gesture-speech relation.…”
Section: Introductionmentioning
confidence: 99%